Study on the stability bearing capacity of multi-column wall in modular steel building. (1st July 2020) - Hou, Jiewen; Wang, Xiaodun; Liu, Jiadi; Chen, Zhihua; Zhong, Xu
Highlights: An innovate multi-column wall was proposed in modular steel building. The stability performance of multi-column modular walls were studied by compression tests. The FE models were established to reproduce stability behavior of multi-column modular walls. Effective length factors of multi-column modular walls were obtained via FE analyses validated by previous tests. Abstract: Modular steel building is an innovative structural system composed of volumetric units that are manufactured with full decoration in factory and assembled on site like building blocks. As one type of steel modular structural system, load-bearing modular structural system of the steel multi-column wall has already been put into engineering practice. However, as the stabilizing mechanism of steel multi-column wall is unclear, effective length factor of column in the existing structural design is conservatively taken as 1.0. In this paper, eight tests were performed to investigate the axial stability performance of modular multi-column walls. The results indicated that the modular wall showed good ductility especially for the one that only experienced overall instability; the greater the width-to-thickness ratio of stand column, the easier it's for local buckling to occur; panel and foamed concrete had minor effects on axial stiffness and ultimate bearing capacity of wall, so they could be neglected in the design. In the end, based on the finite element parametric analysis of steel multi-column wall modular wall, effective length factor of stand columns in the multi-column wall, which could be used in the design, could be obtained. This research could provide a preliminary study on the assessment of the stability capacity of multi-column wall in modular steel building.